2021
DOI: 10.33899/ijvs.2020.127774.1526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different artificial light intensities on some reproductive, productive performance aspects and blood picture of male quail

Abstract: This experiment was designed to determine the influence of various white light intensities on spermatogenesis, hematology and growth performance of male quail. A total of 80 birds of one day aged had been assigned to four equal groups: G1 control group was kept under natural light program 12h light:12h dark. G2, G3, G4 were exposed to artificial white light emitting diodes at 0.6, 45 and 25 Lux for 5 hours daily for 8 weeks starting at 14 days of age. The result showed that the application of Lux 0.6, 45 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The quantity (intensity) and quality (color) of light are two important aspects that influence poultry behavior and productivity (Elkomy et al, 2019). Also, Maty et al (2021) reported that the intensity of white light had a distinct effect on the study parameters, with 0.6 Lux harming the reproductive characteristics, the percentage of lymphocytes and heterophils and the stress index. However, 45 and 25 Lux had a good effect on Male quail component blood.…”
Section: Light Intensitymentioning
confidence: 99%
“…The quantity (intensity) and quality (color) of light are two important aspects that influence poultry behavior and productivity (Elkomy et al, 2019). Also, Maty et al (2021) reported that the intensity of white light had a distinct effect on the study parameters, with 0.6 Lux harming the reproductive characteristics, the percentage of lymphocytes and heterophils and the stress index. However, 45 and 25 Lux had a good effect on Male quail component blood.…”
Section: Light Intensitymentioning
confidence: 99%
“…Chicks of the experiment were fed on a basal diet formulated according to the standard requirements of the broiler (9). The primary and final body weight, entire feed intake/birds, and food conversion ratio (FCR) were assessed weekly to find out any dissimilarities between groups of the experiment (10,11).…”
Section: Growth Performancementioning
confidence: 99%
“…Chicks in the experiment were fed on a basal diet that was formulated according to the standard requirements of broiler [18]. The weight gain was calculated weekly to find out any differences between groups of experiment [19].…”
Section: Average Weight Gain (Wg)mentioning
confidence: 99%